A case of solitary neurofibroma originating in the lower lip. Issue 2 (March 2021) - Hoshino, Teruhide; Shin, Mayu; Kokubun, Katsutoshi; Katakura, Akira
Abstract: Neurofibroma is a benign tumor involving Schwann cells and mesenchymal cells of the nerve sheath. Von Recklinghausen disease is characterized by the occurrence of multiple neurofibroma. However, cases of solitary neurofibroma are rare. Here, we report about a 55-year-old woman who was aware of a mass on her lower lip since 2009; however, she did not seek any medical help owing to lack of other symptoms. Oral findings revealed a tumor of approximately 2 mm in diameter in the median lower lip. Resection was performed under local anesthesia. A spindle-shaped incision was made in the lower lip mucosa, and the mass was bluntly detached from the surrounding tissue and resected as one lump. Detachment was easy and did not extend into the muscle layer. The clinical diagnosis was a benign lower lip tumor (fibroma), and the histopathological diagnosis was a solitary neurofibroma. The wound healed well, and 1 year after the operation, there was no tumor recurrence in the lower lip. Therefore, we report a rare case of solitary neurofibroma on the lower lip.